2013
DOI: 10.1016/j.bpj.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Dynamics of Lyme Disease and Syphilis Spirochetes Reveal Flagellar Torque and Drag

Abstract: The spirochetes that cause Lyme disease (Borrelia burgdorferi) and syphilis (Treponema pallidum) swim through viscous fluids, such as blood and interstitial fluid, by undulating their bodies as traveling, planar waves. These undulations are driven by rotation of the flagella within the periplasmic space, the narrow (∼20-40 nm in width) compartment between the inner and outer membranes. We show here that the swimming speeds of B. burgdorferi and T. pallidum decrease with increases in viscosity of the external a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
(57 reference statements)
3
36
0
Order By: Relevance
“…Rotation of the flagella within the periplasm causes the waveform to propagate, leading to a traveling wave undulation of the entire body (10). Mathematical modeling has shown that the elastic interaction between the flagella and the cell body is sufficient to generate the planar waveform of the bacteria (11) and that rotation of the flagella will lead to traveling wave deformations, similar to what is observed experimentally (12,13). This mathematical modeling suggests that a key factor in determining the shape and motility of B. burgdorferi is the ratio of the flagellar stiffness to that of the cell body.…”
Section: Introductionsupporting
confidence: 48%
See 4 more Smart Citations
“…Rotation of the flagella within the periplasm causes the waveform to propagate, leading to a traveling wave undulation of the entire body (10). Mathematical modeling has shown that the elastic interaction between the flagella and the cell body is sufficient to generate the planar waveform of the bacteria (11) and that rotation of the flagella will lead to traveling wave deformations, similar to what is observed experimentally (12,13). This mathematical modeling suggests that a key factor in determining the shape and motility of B. burgdorferi is the ratio of the flagellar stiffness to that of the cell body.…”
Section: Introductionsupporting
confidence: 48%
“…Interestingly, these bacteria have similar morphologies and motility mechanisms, which suggests that the shape of these bacteria may be extremely important to their ability to invade host tissue. A mathematical model has been developed that can explain the shape and movements of both of these pathogens (11,13,29). Although the model agrees well with the changes in velocity that accompany alterations in the external environment (13), it remains to be shown whether it accurately represents how speed and morphology are affected when the biophysical parameters of the organism are altered.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations